1988
DOI: 10.1073/pnas.85.23.9026
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the cryobehavior of rye protoplasts by modification of the plasma membrane lipid composition

Abstract: Communicated by Andre T. Jagendorf, August 11, 1988 (received for review June 3, 1988 ABSTRACTThe freezing tolerance of protoplasts isolated from nonacclimated rye leaves (Secale cereale L. cv Puma) was significantly altered by using a pH-induced protoplastliposome fusion technique to modify the lipid composition ofthe plasma membrane. The increase in freezing tolerance was elicited by fusion with liposomes composed of either the total phospholipid fraction isolated from the plasma membrane of cold-acclimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 25 publications
2
63
0
Order By: Relevance
“…The production of LTPs with structural characteristics which accommodate di-unsaturated lipid molecules during frost acclimation in barley, is consistent with a role in membrane lipid modification during acclimation. This is reinforced by the known effect of low temperature on the levels of membrane lipid unsaturation (Harwood et al, 1994) and on membrane cryo-behaviour (Steponkus et al, 1988). Further, the molecular dynamics simulation aided modelling of membrane phospholipids into BLT4.9 suggests a conformation (external acyl group) which would facilitate protein membrane interactions and hence lipid exchange between different membranes.…”
Section: Functional Significancementioning
confidence: 97%
“…The production of LTPs with structural characteristics which accommodate di-unsaturated lipid molecules during frost acclimation in barley, is consistent with a role in membrane lipid modification during acclimation. This is reinforced by the known effect of low temperature on the levels of membrane lipid unsaturation (Harwood et al, 1994) and on membrane cryo-behaviour (Steponkus et al, 1988). Further, the molecular dynamics simulation aided modelling of membrane phospholipids into BLT4.9 suggests a conformation (external acyl group) which would facilitate protein membrane interactions and hence lipid exchange between different membranes.…”
Section: Functional Significancementioning
confidence: 97%
“…Increased membrane lipid unsaturation during low temperature exposure has been interpreted as a beneficial acclimation response. Recently, Steponkus et al (26) have moved beyond correlative findings and have definitively shown that increased lipid unsaturation can impart enhanced cryrobehavior to rye plasma membranes. Increased unsaturation of membrane lipids with low temperatures, or conversely decreased fatty acid unsaturation with high temperatures appears to be a mechanism by which biological membranes regulate membrane viscosity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Many plant tissues including potato tubers have been shown to increase the degree of unsaturation of their membrane fatty acids in response to low temperatures (14,15,26,27,30). Increased membrane lipid unsaturation during low temperature exposure has been interpreted as a beneficial acclimation response.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent 'membrane engineering' studies to establish the specific lipid alterations responsible for the differential cryobehavior of the plasma membrane have involved a protoplast x liposome fusion technique (1) to selectively modify the lipid composition of the plasma membrane. Enrichment of the plasma membrane with either mono-or diunsaturated species of phosphatidylcholine transforms the cryobehavior of the plasma membrane such that exocytotic extrusions (rather than endocytotic vesicles) are formed during osmotic contraction, and EIL does not occur during osmotic excursions (13).…”
mentioning
confidence: 99%
“…The objectives of this study were to quantify the progressive increase in freezing tolerance of rye protoplasts and the incidence of the two forms of injury (EIL and LOR) during the cold acclimation process so as to determine when the incidence of EIL first reached a minimum. Further, we wished to determine if artificial enrichment of the plasma membrane with DL2PC, which precludes EIL in NA protoplasts (13) (Fisher Co.) and washed in the appropriate isotonic sorbitol solution. The leaves were cut into small pieces (0.5 to 1 mm in length) and incubated in an isolation medium consisting of 1.3% (w/v) cellulysin (Calbiochem), 0.4% (w/v) macerase (Calbiochem), 0.6% (w/v) potassium dextran sulfate and 10 mm Mes/KOH (pH 5.6) in an isotonic sorbitol solution.…”
mentioning
confidence: 99%